2017
DOI: 10.1017/brimp.2017.13
|View full text |Cite
|
Sign up to set email alerts
|

Misconceptions about Stroke: Causal Attributions for Stroke-Related Symptoms Reflect the Age of the Survivor

Abstract: With visible disabilities, observers tend to overgeneralise from the disability. In contrast, with invisible disabilities such as traumatic brain injury and stroke, observers often fail to allow for challenges resulting from the disability. Persons who have suffered a stroke claim that people misunderstand their symptoms and stigmatise them as a result of these symptoms. This misunderstanding, which happens particularly with young survivors of stroke, may reflect people's causal attributions for symptoms that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 68 publications
(137 reference statements)
0
4
0
3
Order By: Relevance
“…Most stroke survivors live with declined functioning such as poor balance, incontinence, swallowing difficulties, visual disturbances and psychological and cognitive disorders (Jokinen et al, 2015;Wainwright et al, 2017). Hospital readmissions are common after discharge and are associated with increased morbidity, mortality and risk of early institutionalisation (Abreu et al, 2020;Reeves et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most stroke survivors live with declined functioning such as poor balance, incontinence, swallowing difficulties, visual disturbances and psychological and cognitive disorders (Jokinen et al, 2015;Wainwright et al, 2017). Hospital readmissions are common after discharge and are associated with increased morbidity, mortality and risk of early institutionalisation (Abreu et al, 2020;Reeves et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Following the same line of reasoning, other authors (McClure et al, 2008; Wainwright et al, 2017) have found that the public tends to attribute invisible impairments to personality traits of the survivors or the age group to which they belong. Wainwright et al (2017) found that fatigue and depression in group of young people with stroke were attributed to their personality (availability heuristic: ‘he/she is like that’) and not to their stroke. In another study, McClure et al (2008) showed members of the general public photographs of an adolescent survivor of TBI who exhibited behavioural disorders.…”
Section: Attribution Theorymentioning
confidence: 88%
“…Diversos autores (McClure et al, 2008; Stergiou-Kita et al, 2017; Wainwright et al, 2017) han señalado que las secuelas invisibles luego de un DCA son frecuente fuente de estigma público. El estigma público refiere a aquellas actitudes del público hacia los sobrevivientes de un DCA (Foster et al, 2016), y ha sido definido como un complejo constructo social que se origina de la interacción de cuatro componentes: (1) etiquetar diferencias identificadas en una persona; (2) vincular estas diferencias a estereotipos negativos; (3) categorizar a las personas que tienen esta diferencia dentro del exogrupo (‘ellos, las personas con lesión cerebral’) y distinguirlas del endogrupo (‘nosotros, las personas sin lesión cerebral’); y (4) pérdida de estatus y discriminación a las personas del exogrupo (Link & Phelan, 2001).…”
Section: ‘No Soy Quien Creen Que Soy’: Estigma Público Y Daño Cerebra...unclassified
See 2 more Smart Citations